The Effectiveness of Direct Instructional Strategy on Speaking Skills Of 7th Grade At SMP Tri Dharma Palembang - Segara, Bima; Iman, Jaya Nur; Permana, Dio Resta; Angraini, Nike (Fakultas Sastra - Universitas Muslim Indonesia, 2024)
This study was conducted to assess the English speaking proficiency of students. The students' English speaking achievement was abysmal. The aims of this study were to determine: (1) the extent of improvement in speaking skills with and without the use of the direct instructional strategy, and (2) whether there was a notable improvement in the speaking skills of students who received the direct instructional strategy compared to those who did not. This study employed quasi-experimental research methodology. A total of 16 students were selected as a sample, with 16 students assigned to the experimental class and another 16 students assigned to the control class. The data were gathered by the administration of an oral examination. The data were analysed using both paired sample t-tests and independent sample t-tests. Through data analysis, it was determined that there was a notable surge in pupils' proficiency in oral communication. The paired sample t-test yielded a t-test statistic of -28.428 and a significance value of 0.00, which was less than the predetermined significance level of α (0.05). This demonstrates an enhancement in students' oral communication abilities. Furthermore, the results of the independent sample t-test indicate that the calculated t-test value (-13.075) and the corresponding p-value (0.00) were both below the predetermined significance level (α) of 0.05. The results indicate a substantial disparity in the average speaking abilities of pupils who received teaching through the direct instruction technique compared to those who did not get such instruction.